Inflammatory Regulation of CNS Barriers After Traumatic Brain Injury: A Tale Directed by Interleukin-1 - Bodnar, Colleen N.; Watson, James B.; Higgins, Emma K.; Quan, Ning; Bachstetter, Adam D. (Frontiers in Immunology, 2021)
Several barriers separate the central nervous system (CNS) from the rest of the body. These barriers are essential for regulating the movement of fluid, ions, molecules, and immune cells into and out of the brain parenchyma. Each CNS barrier is unique and highly dynamic. Endothelial cells, epithelial cells, pericytes, astrocytes, and other cellular constituents each have intricate functions that are essential to sustain the brain's health. Along with damaging neurons, a traumatic brain injury (TBI) also directly insults the CNS barrier-forming cells. Disruption to the barriers first occurs by physical damage to the cells, called the primary injury. Subsequently, during the secondary injury cascade, a further array of molecular and biochemical changes occurs at the barriers. These changes are focused on rebuilding and remodeling, as well as movement of immune cells and waste into and out of the brain. Secondary injury cascades further damage the CNS barriers. Inflammation is central to healthy remodeling of CNS barriers. However, inflammation, as a secondary pathology, also plays a role in the chronic disruption of the barriers’ functions after TBI. The goal of this paper is to review the different barriers of the brain, including (1) the blood-brain barrier, (2) the blood-cerebrospinal fluid barrier, (3) the meningeal barrier, (4) the blood-retina barrier, and (5) the brain-lesion border. We then detail the changes at these barriers due to both primary and secondary injury following TBI and indicate areas open for future research and discoveries. Finally, we describe the unique function of the pro-inflammatory cytokine interleukin-1 as a central actor in the inflammatory regulation of CNS barrier function and dysfunction after a TBI.